PENERAPAN MEDIA SIMULASI MATLAB BERBASIS INTERACTIVE CONCEPTUAL UNTUK MENINGKATAN PEMAHAMAN KONSEP MAHASISWA - Davi Apriandi; Reza Kusuma Setyansah (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This study aims to know the extent to which the use of Matlab simulation media based conceptual Interactive can overcome the difficulties of students in understanding the Linear Equation System in the course of Numerical Analysis and improve student understanding. This study is a classroom action research, which is carried out in two cycles. Research subjects as many as 25 students grade 7C Prodi Mathematics Education University PGRI Madiun academic year 2016/2017. Research instruments are researchers, learning observation sheets, concept comprehension tests, student response questionnaires and interview guides. Based on the result of the research, it can be concluded that the application of Matlab simulation media based on conceptual interactive in learning can increase the students understanding on Linear Equation System. This is shown by the improvement of students' ability in understanding the system of linear equations in each cycle. The data is also supported by a positive response given by students in learning.